Phytochrome activates the plastid-encoded RNA polymerase for chloroplast biogenesis via nucleus-to-plastid signaling - Chan Yul Yoo (Nature Portfolio, 2019)
Light initiates chloroplast biogenesis by controlling gene expression in plastids. Here Yoo et al. show that nuclear phytochrome signaling triggers plastid gene expression via a novel dual-localized protein necessary for nuclear phytochrome signaling and subsequent anterograde signaling to the plastid.